AB0575 A fulminant case of necrotising fasciitis secondary to rituximab in a patient with rheumatoid arthritis. (23rd January 2014) - Raghuvanshi, S.; Menon, A.
Abstract : Background: Necrotizing fasciitis is a rare rapidly progressive infection along the fascial planes causing fascial necrosis and thrombosis of the subcutaneous blood vessels, leading to cutaneous gangrene. It is associated with extremely high mortality ranging from 30% with treatment to, 100% without surgical debridement 1 . We present a case of a patient with Rheumatoid arthritis who presented with necrotising fasciitis secondary to herpes zoster infection affecting her left arm, 18 days after her first cycle of Rituximab treatment. Rituximab is an anti CD20 antibody which results in programmed apoptosis of B Lymphocytes and complement mediated cytotoxicity with a half-life between 1.6 to 20 days and can be detected up to 6 months after the infusion 3 . Results: 62 years old female with long standing sero-positive rheumatoid arthritis having failed multiple disease modifying treatments (DMARDs) and had developed interstitial pneumonitis on methotrexate and leflunomide combination for which she had been commenced on oral prednisolone. She was on a stable dose of 15 mgs daily for 6 months when she commenced Rituximab therapy and she presented with extremely swollen painful left arm 18 days after the second pulse of her 1st cycle of Rituximab. The symptoms developed over 12 hours with no history of preceding trauma, she had one episode of rigors at home before presentation. Her left arm had evidence of early vesicles and swelling but no obvious rash, she was in a lot of pain. An initial working diagnosis of atypical herpes zoster infection with cellulitis secondary to immunosuppressive therapy was made. Initial treatment involved intravenous acyclovir with IV Tazobactam. On admission, features of sepsis were present with a temperature of 38.1°C, pulse 125 beats per minute, BP 108/70 mmHg and oxygen saturation of 96%. Within a few hours a red blotchy erythematous rash developed in surrounding skin and excruciating pain in her arm with evidence of septic shock with radiographs of her left arm and forearm failing to show any evidence of gas in soft tissue. She was transferred immediately to ITU in view of her clinical deterioration with working diagnosis of necrotising fasciitis secondary to herpes infection. A surgical review was initiated and eventually she had fasciotomy to her left arm. Intraoperative specimens and tissue swabs isolated Group A streptococcus. Unfortunately her condition worsened needing ventilation, heavy inotropic support, she developed acute kidney injury with subsequent pulseless electrical activity cardiac arrest. Conclusions: Necrotising fasciitis is rare, rapidly progressive and life threatening emergency with patients on immunosuppressive therapy being at great risk. A high index of clinical suspicion and initiation of definitive management, appropriate antimicrobial therapy and surgical debridement, at the earliest opportunity may help prevent loss of life or extensive surgical debridement. The diagnosis is made on clinical grounds with radiographic findings noted to be inconsistent, the classic appearance of gas in soft tissue is only seen in only a minority of patients 4 . References: Harrison's textbook of Medicine (2008) Volume 2. Nice Guidelines Rheumatoid Arthritis-drug treatment after failure of a TNF inhibitor (TA195). D.T. Selewskia, G.V. Shahc, et al. Rituximab (Rituxan). AJNR2010 31:1178-1180. Rehman J. Kaynan A. et al Journal of Urology. 162(6):2101, 1999 Dec. Disclosure of Interest: None Declared